2009
DOI: 10.1111/j.1745-4514.2009.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT ACTIVITY AND TOTAL PHENOLIC CONTENTS IN PEEL AND PULP OF CHINESE JUJUBE (ZIZIPHUS JUJUBAMILL) FRUITS

Abstract: Total phenolic contents in peel and pulp of the fruits of three Chinese jujube cultivars (Ziziphus jujuba cv. mayazao, Z. jujuba cv. dongzao and Z. jujuba cv. yuanzao) were determined. The antioxidant activities in peel and pulp of the jujube fruits were measured by different methods, including 2,2‐Diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging capacity, ferric reducing antioxidant power (FRAP) and Trolox equivalent antioxidant capacity (TEAC). The total phenolic content in peel was five to six times high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 30 publications
5
45
0
1
Order By: Relevance
“…Also, both total phenolics and total flavonoids were the major functional components in water extract of peel (PW), while oleanolic acid, carotenoid and chlorophyll were the main bioactive compounds in ethyl acetate extract of Luffa peel (PA). A similar outcome was reported by Wolfe, Wu, and Liu (2003) and Xue, Feng, Cao, Cao, and Jiang (2009), showing that a higher level of total phenolics was in apple peel and Chinese jujube skin than pulp, respectively. It may be postulated that phenolic compounds can be accumulated in the epithelial tissue of plants for protection against oxidative damage (Toor & Savage, 2005).…”
Section: Functional Components In Luffa Pulp and Peelsupporting
confidence: 86%
“…Also, both total phenolics and total flavonoids were the major functional components in water extract of peel (PW), while oleanolic acid, carotenoid and chlorophyll were the main bioactive compounds in ethyl acetate extract of Luffa peel (PA). A similar outcome was reported by Wolfe, Wu, and Liu (2003) and Xue, Feng, Cao, Cao, and Jiang (2009), showing that a higher level of total phenolics was in apple peel and Chinese jujube skin than pulp, respectively. It may be postulated that phenolic compounds can be accumulated in the epithelial tissue of plants for protection against oxidative damage (Toor & Savage, 2005).…”
Section: Functional Components In Luffa Pulp and Peelsupporting
confidence: 86%
“…De Oliveira et al (2009) studied TP in methanolic extract powders of acerola, pineapple and passion fruit industrial residues, including pulp, seeds and peel, and found values of 681, 271 and 103 mg of GAEs/100 g of dry weight respectively. The literature consulted reports studies of antioxidant capacity and total phenols in peel fruits such as jujube (Xue, Feng, Cao, Cao, & Jiang, 2009), banana (González-Montelongo, Gloria Lobo, & González, 2010, nectarine, plum and peach (Tomas-Barberan et al, 2001), and apple (Kunradi Vieira et al, 2009). According to these studies, the phenols content and antioxidant activity in peels is higher than in pulp.…”
Section: Non-edible Portion Of the Fruits (Seed And Peel)mentioning
confidence: 99%
“…The apple polyphenol extract (APE) was concentrated in vacuo at 30 8C in a rotavapor and dissolved with 10 mL distilled water, speed vacuumed to dryness, and stored at À80 8C until further use. The total phenolic content was determined by the method of Xue et al (2009) and diluted to the concentration required before use.…”
Section: Preparation Of Apple Polyphenol Extractmentioning
confidence: 99%